(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The performance and efficiency of the dust holders analyzed indicate that the efficiency of cleaning these dust holders is much lower, and the main reason for this is in the uncertainty of how the content of the dust air being cleaned is associated with the efficiency of cleaning dust holders.